Hydrogeological Characterization of the Gunungsewu Karst Area in the Upper Reach of Gremeng Karst Drainage Basin, Indonesia - Cahyadi Ahmad (EDP Sciences, 2021)
The definition of a karst drainage basin in the aquifer of the karst area is an absolute thing to do as a water resource management unit. This research aimed to characterize the hydrogeology of the Gunungsewu Karst Area in the upper reach of the Gremeng Karst Drainage Basin. For this purpose, it was divided into three stages, namely geological survey, speleological survey, and artificial tracer test. The results indicate that the area observed lies in two or more geological formations: Semilir Formation, composed of sandstone and tuff from the ancient volcano Wonodadi eruptions, and Wonosari Formation, in which carbonate rocks consisting of massive coral limestone and bedded chalky limestone predominate. In volcanic rocks, the surface rivers have developed into allogenic streams flowing from underlying beds exposed updip. The contact between the two different formations results in the formation of ponors and springs. The artificial tracer test revealed two underground river systems with single conduits controlled by the allogenic rivers and large slope gradients in the study area.